Prevalence of Bacteriuria in Infants Suffering from Acute Gastroenteritis - R.H. Sardjito D.; Iman T. Rachman; Soeparto P.; Nurasid H.; Soebagjo B. (Paediatrica Indonesiana, 1978)
Urinary tract infection in infancy when not early recognized can frequently cause parenchymal damage of the kidney. Symptoms like nausea, vomiting, fever and diarrhea in most instances resemble those of gastroenteritis. A survey conducted from November to December 1975 on 25 infants admitted to the Dr. Soetomo Hospital Surabaya with acute gastroenteritis showed an incidence of b1acteriuria in 8 patients (32%) with a colony count of more than 10^5/mmÂ³ urine, of which 6 were of E. Coli type and 2 of Aerobacter Aerogenes type. Related to this fairly high incidence of bacteriuria in gastroenteritis, further evaluations of the exact role of urinary tract infection in causing infantile diarrhea diseases are mandatory.